(3GdJbhje GdELJeGYj ddeTQhYGJ (B:s (3eQLY aj JMdjd GdLOhi (B/s - (3HjQS, Oj Hdjhs; (3GdSHGNj, eMeO MeOj s; (3S(B.(3Gjg(B.(3fGTs ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 1994)
(3GdCSGS GdefWbj dJMdjd GdLOhi, CSS GdQaGgjI aj JMdjd GdLOhi, eYGjjQ GdESJKeGQ aj GdbWGY GdYGe, GdeNGWQI hYOe GdJbjf, Jbhje GdJcGdja hGdefGaY YfO JZjQ GdCSYGQ, JSYjQ GdXd, GdCKGQ GdNGQLjI hGdSdY GdYGeI, SYQ GdNUe GdELJeGYj, GdJbhje GdELJeGYj ddeTQhYGJ aj GdOhd GdfGejI, GdJWHjb GdYedj dJMdjd GdLOhis
(3HHdjhZQGajG(B: (3U(B.347s
Keywords: (3GdeTQhYGJs; (3Jbjje GdCOGAs